Identification and in silico Characterization of Deleterious Single Nucleotide Variations in Human ZP2 Gene - Rajput, Neha; Gahlay, Gagandeep Kaur (Frontiers in Cell and Developmental Biology, 2021)
ZP2, an important component of the zona matrix, surrounds mammalian oocytes and facilitates fertilization. Recently, some studies have documented the association of mutations in genes encoding the zona matrix with the infertile status of human females. Single nucleotide polymorphisms (SNPs) are the most common type of genetic variations observed in a population and as per the dbSNP database, around 5152 SNPs are reported to exist in the human ZP2(hZP2) gene. Although a wide range of computational tools are publicly available, yet no computational studies have been done to date to identify and analyze structural and functional effects of deleterious SNPs on hZP2. In this study, we conducted a comprehensive in silico analysis of all the SNPs found in hZP2. Six different computational tools including SIFT and PolyPhen-2 predicted 18 common nsSNPs as deleterious of which 12 were predicted to most likely affect the structure / functional properties. These were either present in the N-term region crucial for sperm-zona interaction or in the zona domain. 31 additional SNPs in both coding and non-coding regions were also identified. Interestingly, some of these SNPs have been found to be present in infertile females in some recent studies.